Challenges in Human Capital Development in Disaster Prevention and Mitigation in Thailand - Wichaipa, Kanrawee (Prosiding Seminar, 2021)
This article aims to develop and develop human capital in the areas of disaster prevention and mitigation in Thailand. to see the scenario of the implementation to competency systems in the development of human capital in the public sector. This is a case study that deals with the coordination between the state department and the central state and local government organizations in the framework of Fragmented Centralism. Thus, it is challenging in collaborative governance between central and local states, which is the management of the government in the present era known as the â€œGovernanceâ€ in which the government must work together to provide public services to the people efficiently according to the needs of the people appropriately.